The role of the cultural economics in the development of Bulgarian wine tourism - Velinov, Ivo Iv. (Annual of Natural Sciences Department, 2021)
The author of this report examines basic concepts in the field of wine tourism. The main theoretical ideas, embedded in the cultural economics, aim to represent the dynamics of economic and cultural processes in the tourism industry. The first part of the report outlines thematic assumptions about the role of culture and economy in the wine industry as prerequisites for the development of wine tourism. Therefore, aspects of the emotional, practical and intellectual experience of wine cultural landscapes are analyzed using theoretical statements in the cultural economics. The thematic study summarizes the result of the current cultural and economic situation of wine tourism in relation to Bulgarian natural and anthropogenic tourism resources.